Business Group Affiliation, Board Quality and Audit Pricing Behavior: Evidence from Indian Companies. Issue 2 (22nd February 2016) - Johl, Shireenjit K.; Khan, Arifur; Subramaniam, Nava; Muttakin, Mohammad
Abstract : This study examines the relationships among business group affiliation, board quality and audit fees in an emerging market setting. Using data from Indian firms listed on the Bombay Stock Exchange (BSE) over a nine‐year period (2004–2012), our results indicate that firms affiliated with a business group pay higher audit fees than those without such affiliations. We also find that group‐affiliated firms with higher‐quality boards pay relatively higher audit fees compared to other counterparts. Further, our findings suggest that group‐affiliated firms pay lower fee premiums when an audit is undertaken by a Big 4 firm or its affiliates, which implies that economies of scale may be a potential competitive advantage held by larger auditors. The results of the study have implications for the management of audit fees by group‐affiliated firms through board structure and processes.